PERAN KOMUNIKASI PARIWISATA DALAM INTERPRSTASI WISATA BUDAYA DI DESA BANTAR AGUNG, MAJALENGKA JAWA BARAT - Elmi Nurvianti; R. Dewi Mutia Farida Farida; Gurruh Dwi Septano; Reni Reni; Santos Winarso Dwiyogo (JURNAL ABDIMAS PLJ, 2026)
This community service activity focuses on developing tourism villages through improving tourism communication strategies. This activity aims to make partners a model for sustainable community economic growth through the potential of tourism villages in Bantar Agung village, Majalengka, West Java. With a tourism communication strategy. The community empowerment program is at the core of this activity by implementing a community based tourism approach where partners are placed as the main actors at every stage of planning, implementation, and evaluation of programs in tourism communication. The approach taken in this community service activity is based on the principle of community independence, this method aims to make partners understand tourism communication, be able to explain tourist friendly services, and understand the role of the community as host, also can strengthen the ability of tourism village managers in managing visitors with hospitality and profesionalism. The target output of this community service activity is one article published in electronic media, activity videos and increasing partner empowerment.